Please help with geometry

Accepted Solution

For this question, the formula we'll be using is the Pythagorean theorem ( [tex]a^{2} +b^{2} =c^{2}[/tex] ).So lets find out the missing length x?First lets find the missing length of the right triangle, to the right.We can label the first side (3), as "A", the second side (8), as B.That would look like, when plugged in the equation:[tex]3^{2} +8^{2}=c^{2}[/tex]We need to solve for "c".3 squared is equal to 9.8 squared is equal to 64.9+64 = 73[tex]73=c^{2} \\[/tex]Unsquared both sides (square root)[tex]\sqrt{73} =c[/tex]--------------We found one side, we can use to find "x".Now lets follow the same process, with the triangle to the left. [tex]a^{2} +b^{2} =c^{2}[/tex]-Plug in following numbers:[tex]6^{2} +(\sqrt{73})^{2} =c^{2} \\36+73=c^{2} \\109=c^{2} \\\\\\\sqrt{109} =c[/tex]so [tex]x=\sqrt{109}[/tex]----------#Team Trees #Team Seas #PAW #Spread_Positivity I hope this helps, -Oceanbreeze24